The Impact of Employee Personality and Customer Orientation on Customer Incivility in the Service Industry - Yuda Surya Pratama; Ahmad Hudaiby Galih Kusumah; Sri Marhanah (Research and Community Service Center, Politeknik Pariwisata NHI Bandung, 2025)
This study investigates how employee personality traits and customer orientation influence customer incivility in the service industry, emphasizing the mediating role of customer orientation. Drawing on the Big Five Personality framework, it explores how conscientiousness, agreeableness, and core self-evaluation (CSE) shape employee interactions with customers. The findings show that conscientiousness and agreeableness significantly enhance customer orientation, while CSE is positively linked to selling orientation but has no notable effect on customer orientation. Customer orientation emerges as a key mediating variable that links personality traits to the ability to manage customer incivility. Using a quantitative method, data were collected from 218 frontline employees across various service sectors. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the proposed relationships. The model revealed that personality traits and customer orientation explain only 3.2% of the variance in customer incivility, highlighting the multifactorial nature of this issue and indicating the need to consider broader variables such as workplace climate, emotional labor demands, and organizational support. This research contributes to the literature by demonstrating the indirect influence of personality traits on customer incivility and affirming the importance of customer orientation in service roles. It recommends prioritizing recruiting individuals high in agreeableness and conscientiousness and implementing training programs that foster emotional intelligence and conflict management skills. Additionally, it calls for future research to examine moderating and mediating variables, such as job autonomy, peer support, and cultural context, to develop a more comprehensive understanding of managing customer incivility in diverse service environments.